Penerapan Teknologi Pompa Air Tenaga Surya dan Aplikasi Pembukuan Mobile pada Usaha Pertanian di Bunton - Supriyono, Supriyono; Purwiyanto, Purwiyanto; Riyanto, Sugeng Dwi (Madani : Indonesian Journal of Civil Society, 2026)
The Kreasi Tani Group in Bunton Village, Cilacap Regency, faces two main challenges in developing oyster mushroom cultivation and pioneering shallot cultivation. First, the significant water requirement for mushroom spraying and shallot seedling watering causes quite burdensome electricity costs for water pump operations. Second, the farmer group does not yet have an adequate financial bookkeeping system, making it difficult for them to accurately monitor financial conditions and make strategic considerations for future business development. This community service activity aims to implement two technological solutions. The first solution is to design and install a Solar power plants system to operate the water pump. Solar power plants system uses 2 200 Wp photovoltaic units, 1 1500 VA inverter unit, and 2 60 AH batteries. The second solution is to develop and train the use of an Android-based mobile bookkeeping application (created with MIT App Inventor) designed to record production results, prices, and summarize sales results of oyster mushrooms and shallots periodically (weekly or monthly). The implementation of Solar Power Plant system can significantly reduce production costs through electricity savings. Meanwhile, mobile bookkeeping applications make it easier for managers to create financial reports, provide accurate data sources, and support strategic decision-making for future business development.